2018
DOI: 10.1089/dna.2017.3922
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 Inhibitors Modulate Biological Functions of Gastric Cancer Cells via PTEN/PI3K/mTOR Pathway

Abstract: Gastric cancer is one of the most common malignancy in the world. microRNAs (miRNAs) are naturally occurring noncoding RNA that control gene expression by targeting messenger RNA (mRNA) for post-transcriptional repression or cleavage. This study focused on a specific miRNA, miR-21, which was overexpressed in gastric cancer and examined the effects of miR-21 inhibitor on biological functions of gastric cancer cells and its possible mechanism. Gastric cancer cells MKN74 were treated with miR-21 inhibitor, negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Previous studies demonstrated that miR-21-5p plays a tumor-promoting role in many types of cancer. It functions by regulating several oncogenic pathways such as PI3K/AKT and modulating matrix metalloproteases (25,26). Consistently, we found that miR-21-5p was upregulated in gastric cancer tissues and miR-21-5p expression was associated with tumor grade, and exhibited high expression in high-grade tumors and low expression in low-grade tumors.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies demonstrated that miR-21-5p plays a tumor-promoting role in many types of cancer. It functions by regulating several oncogenic pathways such as PI3K/AKT and modulating matrix metalloproteases (25,26). Consistently, we found that miR-21-5p was upregulated in gastric cancer tissues and miR-21-5p expression was associated with tumor grade, and exhibited high expression in high-grade tumors and low expression in low-grade tumors.…”
Section: Discussionsupporting
confidence: 77%
“…RECK, reversion-inducing-cysteine-rich protein with kazal motifs; SP1, specificity protein 1; TSC1, tuberous sclerosis 1; VEGFA, vascular endothelial growth factor A. migration of GC cells by directly binding to the 3'-UTR of PTEN. Whereas antisense oligonucleotides against miR-21 were able to increase PTEN expression and impair downstream PI3K/Akt/mTOR signaling, leading to reverse effects on these biological behaviors of GC cells (27,69). In addition, miR-21 was involved in the regulation of a number of Polycomb group (PcG) proteins on gastric cancer stem cells (CSCs), a small subset of cancer cells with self-renewal and tumor-initiating properties, which are critical in tumor metastasis, recurrence and chemoresistance (70).…”
Section: Pten Mediates Oncogenic Activities Of Mirnas Via Pi3k/akt Simentioning
confidence: 99%
“…MiR-21, miR-450 and miR-149 participating in the regulation of glaucoma have been reported [14]. Moreover, miR-21 and miR-149 are associated with the development of gastric cancer [12,13]. More importantly, given the glaucoma exhibited similar cancer type with gastric cancer, hence, we explored the roles of miR-450 in gastric cancer and miR-450 was con rmed to be a tumor suppressor in gastric cancer.…”
Section: Discussionmentioning
confidence: 98%
“…MiR-582-5p inhibits cell proliferation and promoted apoptosis by regulating AKT3 [6]. Other studies have also shown the inhibitory effect of miRNAs on the progression and development of gastric cancer, including miR-744, miR-140-5p, miR-181a, miR-182, miR-802, miR-21, miR-149 [7][8][9][10][11][12][13]. On the other hand, miR-450, as a novel miRNA, which function as a tumor suppressor in the regulation of glaucoma [14].…”
Section: Introductionmentioning
confidence: 99%